HYBRID LEARNING DALAM PELATIHAN ASESOR DI BAN-PDM PROVINSI JAWA TIMUR - Dinda Dzurrotun Nafisah (Jurnal Manajemen Pendidikan, 2025)
This study aims to analyze the application of hybrid learning in assessor training at BAN-PDM East Java Province with a focus on three aspects, namely the importance of hybrid learning in assessor training, the hybrid learning approach in assessor training, and the impact of applying hybrid learning in assessor training. This study uses a qualitative research method with a descriptive approach. The data collection techniques included interviews, observation, and documentation. The results of this study indicate that hybrid learning is not only a solution to budget constraints but also effective in maintaining the continuity of the process of updating assessors' understanding. The training strategy was carried out through a combination of synchronous learning (virtual face-to-face sessions via Zoom) and asynchronous learning (independent assignments via LMS and the official website). The implementation of hybrid learning has been proven to increase cost efficiency, time flexibility, and participant accessibility, although there are still challenges in the form of participants' lack of focus during online sessions. Overall, the implementation of hybrid learning in assessor training at BAN-PDM provides significant benefits for improving assessor professionalism while supporting the quality of the accreditation process.